Tailoring interpersonal psychotherapy to psycho-oncology patients (TIPTOP): feasibility study protocol - Laing, Ebba; Acebo de Arriba, Rita; Schramm, Elisabeth; Schäffeler, Norbert; Zipfel, Stephan; Stengel, Andreas; Graf, Johanna (Frontiers in Psychiatry, 2025)
ObjectivePatients with cancer suffering from comorbid symptoms of depression need a psychotherapeutic treatment that is specifically tailored to the exceptional context of acute or chronic cancer treatment. The conceptualization of depression in Interpersonal Psychotherapy (IPT) is a promising framework for symptoms of depression in patients with cancer, because it focuses on coping with stressful life events, managing change and accessing social support.MethodThe intervention was developed based on standard practice of group IPT for depression and adapted to the oncology setting by an expert panel. The IPT intervention comprises 10 weekly sessions of 60 minutes each. It is structured into modules incorporating IPT core themes: role transitions, grief, connection and interpersonal conflict. This feasibility study with an integrated qualitative study seeks to ascertain feasibility and acceptability of a larger trial of modified group IPT for adult patients with cancer within the context of a university clinics’ outpatient treatment. In addition, the study will enable first evidence of the intervention’s efficacy in reducing symptoms of depression and anxiety, and changes in interpersonal factors such as loneliness, thwarted sense of belonging, perceived burdensomeness, and perceived social support. Post-intervention semi-structured interviews will be recorded for qualitative content analysis.ConclusionOur findings will suggest whether investigating group IPT as proposed is an acceptable, feasible and safe approach to ameliorate symptoms of depression in patients with cancer. The study is innovative in that it provides a new treatment to patients of different cancer types and treatment stages, creating a setting that is naturalistic and realistic in the context of psycho-oncology services.